Aromatase inhibitors in ovarian cancer: is there a role?. Issue 4 (1st July 2008) - Li, Y. F.; Hu, W.; Fu, S. Q.; Li, J. D.; Liu, J. H.; Kavanagh, J. J.
Abstract : Estrogen plays a role in ovarian tumorigenesis. Aromatase is the enzyme required for the synthesis of estrogen via conversion of androgen to estrogen, which is the major source of estrogen in postmenopausal women. Aromatase is present in normal ovaries and other tissues (e.g., fat and muscle) as well as in 33–81% tumor tissues of ovarian cancer. Aromatase inhibitors (AIs) block estrogen synthesis by inhibiting aromatase activity. In patients with recurrent ovarian cancer, single-agent AI therapy has been shown to elicit clinical response rates of up to 35.7% and stable disease rates of 20–42%. Given the limited treatment options for recurrent ovarian cancer and the favorable safety profile and convenient use, AI is a rational option for prolonging platinum-free interval in recurrent ovarian cancer. Further studies are required to determine the efficacy of combination treatment with AIs and biological agents, determine the benefit of AIs for treating special types of ovarian cancer (e.g., endometrioid type), and identify biomarkers for targeted patient selection. This review summarizes the current epidemiologic, preclinical, and clinical data regarding estrogen's role in ovarian cancer, the expression and regulation of aromatase in this disease, the development and characteristics of the three generations of AIs, and the preclinical and clinical studies of AIs in the treatment of ovarian cancer.